EVALUASI RENCANA KERJA SATUAN KERJA PERANGKAT DAERAHBADAN PERENCANAAN PEMBANGUNAN DAERAH KOTA SEMARANG - R Slamet Santoso (Departemen Administrasi Publik, Universitas Diponegoro, 2016)
Departing from the problems of weak evaluation planning at local government level work unit, we conducted this study with the aim to get an overview of the evaluation work plan on working units, and the formulation of solving the problem and provide solutions. This research was conducted with a qualitative approach, using in-depth interviews and documentation of data, and then analyzed with domain analysis techniques.The results showed evaluation work plan in Bappeda still not effective. Bappeda only to evaluate the results of the work plan at this stage, while at the policy and implementation stages have not been carried out. Some of the main problems found in the evaluation work plan Bappeda are no guidelines for internal evaluation work plan, limited information technology support, the limited number and quality planners, and not the good aspects of the legality of the work plan.Recommendations for addressing concerns in Bappeda evaluation work plan are: strengthening the commitment of the planning; the establishment of guidelines for the evaluation of the work plan, the data developing regional planning system; to improve coordination, communication and development planning; increased monitoring of the quarter; utilization of evaluation results; and improving the quality and welfare of workers planner.